1999
DOI: 10.1017/s0958067099018412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypocalcaemia on Glucose Metabolism in Hyperketonaemic Piglets

Abstract: In nine 2- to 3-month-old hyperketonaemic piglets the kinetics of glucose and D-beta-hydroxybutyrate (D-BHB) metabolism were studied during hypo- and normocalcaemia in paired experiments. Hyperketonaemia (1.3 and 2.5 mmol D-BHB (l plasma)-1) was generated by a stepwise increase of DL-BHB infusion. Hypocalcaemia spontaneously developed in five piglets due to an inherited calcitriol deficiency and was induced in four control piglets by a continuous infusion of Na2-EDTA. The method of single isotopic marker injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The possible reasons for this adaptive response of the pregnant ewes have been discussed in the previous section. These observations are in agreement with results from our own previous studies which showed that glucose flux into peripheral tissues was decreased in hyperketonemic hypocalcemic piglets (Schlumbohm and Harmeyer, 1999). We conclude from these results that hypocalcemia exerts an extraregulatory strain upon the pregnant ewe.…”
Section: Possible Sequence Of Events Of Hypocalcemia On Glucose Metabolismsupporting
confidence: 93%
See 4 more Smart Citations
“…The possible reasons for this adaptive response of the pregnant ewes have been discussed in the previous section. These observations are in agreement with results from our own previous studies which showed that glucose flux into peripheral tissues was decreased in hyperketonemic hypocalcemic piglets (Schlumbohm and Harmeyer, 1999). We conclude from these results that hypocalcemia exerts an extraregulatory strain upon the pregnant ewe.…”
Section: Possible Sequence Of Events Of Hypocalcemia On Glucose Metabolismsupporting
confidence: 93%
“…It was purchased from Du-Pont de Nemours (Dreieich, Germany). Na-DL-βhydroxybutyrate was synthesized as described pre- viously (Schlumbohm and Harmeyer, 1999). The chemicals used for determination of the fraction of the D-βhydroxybutyrate (D-BHB) isomer in the DL-racemate, were the same as described previously (Schlumbohm and Harmeyer, accepted).…”
Section: Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations